Mixing musics : Turkish Jewry and the urban landscape of a sacred song - Jackson, Maureen (Maureen Barbara) (Stanford studies in Jewish history and culture., 2013)
Through Ottoman, Turkish, and Jewish music-making this cultural history illuminates a multi-ethnic Ottoman art world and its transformations across the twentieth and twenty-first centuries. It explores cross-cultural flows often left out of histories focusing on Jewish communities in isolation, top-down political events, or national narratives. The genre under study, Maftirim music, is a paraliturgical sacred suite developing since the seventeenth century along with Ottoman court music.